Effects of IBGE's 2019 Biomes Definition on Different Political-Administrative Scales in Brazil - Pedro Ribeiro Andrade; Aline Cristina Soterroni; Gustavo Felipe Balué Arcoverde; Maria Isabel Sobral Escada (Revista Brasileira de Cartografia)
In 2019, the official delimitation of the Brazilian biomes was updated to a considerably more detailed description compared to the previous definition that lasted 15 years. This work investigates the possible effects of such changes in different political-administrative scales, ranging from biomes to the municipality level. We define effect levels according to the changes between the biomes in each scale, indicating the areas more subject to the changes in the newest version of the Brazilian biomes. Depending on the scale of the study, the changes in the Brazilian biomes  might have significant effects, mainly in the Pampa biome, in Piauí, São Paulo, Sergipe, and Bahia states, and at the municipality level.